Efficiency of Inhaled Cannabidiol in Cannabis Use Disorder: The Pilot Study Cannavap - Cleirec, Grégoire; Desmier, Esther; Lacatus, Cristina; Lesgourgues, Simon; Braun, Anais; Peloso, Claire; Obadia, Chanaëlle (Frontiers in Psychiatry, 2022)
Introduction Cannabidiol (CBD), the second most prevalent cannabinoid found in cannabis, is considered to be safe for use. Studies suggest that CBD may be of benefit in treating cannabis use disorder (CUD). In clinical practice, CBD is already being used by patients who are trying to reduce or stop their cannabis consumption. The aim of this study was to assess the potential of CBD inhaled using a vaping device in CUD. Methods This was an exploratory, observational, non-randomized, open-label study conducted at an Addiction Support and Prevention Center in Paris. The primary endpoint was a reduction of at least 50% in the reported number of joints consumed daily at 12 weeks. The participants were given an electronic cigarette along with liquid containing CBD. Nicotine at 6 mg/ml could be added in case of co-consumption of tobacco. They were assessed once a week and the CBD liquid dose was adjusted based on withdrawal signs and cravings (33.3, 66.6 or 100 mg/mL). Results Between November 2020 and May 2021, 20 patients were included and 9 (45%) completed the follow-up. All of the participants used tobacco, and were provided a liquid with nicotine. At 12 weeks, 6 patients (30%) had reduced their daily cannabis consumption by at least 50%. The mean number of joints per day was 3, compared to 6.7 at baseline. The mean amount of CBD inhaled per day was 215.8 mg. No symptomatic treatment for cannabis withdrawal was prescribed. Mild adverse effects attributable to CBD and not requiring the prescription of any medicines were reported in a few patients. Conclusion This research provides evidence in favor of the use of CBD in CUD. It also highlights the benefits of inhalation as the route of CBD administration in patients who use cannabis: inhalation can allow users to self-titrate CBD based on their withdrawal symptoms and cravings. This study illustrates the interest of proposing an addictological intervention targeting at the same time tobacco and cannabis dependence in users who are co-consumers. A double-blind, randomized, placebo-controlled clinical trial is needed to assess the efficacy of inhaled CBD in CUD. Study registration number (IDRCB) issued by the ANSM (Agence nationale de sécurité du médicament et des produits de santé—French National Agency for Medicines and Health Products Safety): 2018-A03256-49. This study received IEC approval from the CPP Sud-Ouest et Outre-Mer 1 (South-West and Overseas 1 IEC) on 15/06/2020 (CPP 1-19-041/ID 3012).